3D angle-interlock woven fabric based on plain group P4mm symmetry. (1st January 2020) - Ma, Wensuo; Liu, Kui; Fan, Weifeng; Huang, Zhaohua; Yin, Jianjun
Abstract: A unit composed of the intersected yarns was deduced by the symmetry operation which was described by the element of the plain point group 4 mm. The geometric of novel fabrics was discussed based on whole symmetries of plain group P 4mm, which was analogous to the traditional angle-interlock woven fabrics. The elastic properties of this fabrics could be designed to be orthogonal isotropic. The analysis results indicated that the fiber volume fraction of the fabrics increased with the increment of the deformation coefficient of structural yarns by established its mathematical model. The feasible processing technology of novel angle-interlock woven was discussed and validated by experiment. Clearly different from traditional angle-interlock woven fabrics, the weft yarns were equally crooked as the warp yarn in these fabrics. The novel structural fabrics as a reinforced phase were beneficial to homogenize the in-plane properties of composites. The proposed fabrics were a basis in developing novel fiber reinforced composites. The mathematical model of the novel 3D angle-interlock composites was established based on point group matrix representation to predict elastic properties, the tensile modulus of elasticity was verified by experiments and its particularity was analyzed. The tensile properties of the novel 3D angle-interlock composites were compared with other three composites, the results shown that the novel 3D angle-interlock composites had stable modulus, high strength and good toughness.